Living Law dalam KUHP Baru: Tantangan Integrasi antara Hukum Negara, Hukum Adat, dan Prinsip Kepastian Hukum - Muliadi Nur (Bahasa Indonesia, 2026)
The enactment of the new Indonesian Criminal Code (KUHP) in 2023, which will take effect in 2026, marks a significant milestone in the decolonization of national criminal law through the explicit recognition of living law (hukum yang hidup dalam masyarakat) as a source of criminal liability. This recognition, however, presents complex challenges in integrating unwritten customary law into a formal state legal system grounded in the principle of legal certainty. This article aims to critically analyze the normative construction of living law within the new KUHP and identify the multifaceted challenges of its integration. Employing a normative legal research method with statutory and conceptual approaches, this study finds that the integration faces substantial hurdles across normative (the paradox of formalizing unwritten law), procedural (the incompatibility of adat procedures with formal criminal procedure), ideological (alignment with human rights and constitutional principles), institutional (the capacity of law enforcement), and sociological dimensions. The study concludes that while the recognition of living law is progressive, its successful implementation requires a balanced model of integration that respects the dynamic character of customary law, ensures legal certainty through limited formalization and jurisprudence, and strengthens the institutional bridge between state and customary justice systems